The handbook of English pronunciation - Reed, Marnie; Levis, John (John M.) (Malden, MA : Wiley Blackwell, 2015)
'The Handbook of English Pronunciation presents a comprehensive exploration of the characteristics of English pronunciation, including language acquisition, English in the world, its relationship to modern technology, the shifting role of accent, and more'--
Machine generated contents note: Table of Contents Notes on Contributors Introduction A. The History of English Pronunciation 1. The historical evolution of English pronunciation (Jeremy Smith, UK) 2. Accent as a social symbol (Lynda Mugglestone, UK) 3. History of ESL Pronunciation Teaching (John Murphy, US and Amanda Baker, Australia) B. Describing English Pronunciation 4. Segmentals (David Deterding, Brunei) 5. Syllable structure (Adam Brown, New Zealand) 6. Lexical stress in English pronunciation (Anne Cutler, The Netherlands) 7. The Rhythmic Patterning of English(es): Implications for Pronunciation Teaching (Ee Ling Low, Singapore) 8. English Intonation -- Form and Meaning (Anne Wichmann, UK and John Levis, US) C. Pronunciation and Discourse 9. Connected speech (Ghinwa Alameen, Syria and John Levis, US) 10. Functions of intonation in discourse (Anne Wichmann, UK) 11. Pronunciation in the analysis of discourse (Beatrice Szczepek Reed, UK) 12. Fluency (Ron Thomson, Brock University, Canada) D. Pronunciation of the major varieties of English 13. North American English (Charles Boberg, Canada) 14. British English (Clive Upton, UK) 15. Australian/New Zealand English (Laurie Bauer, New Zealand) 16. The Pronunciation of English in South Africa (Ian Bekker, Zambia and Albertus van Rooy, Zambia) 17. Indian English Pronounciation (Pramod Pandey, India) 18. Pronunciation and World Englishes (Cecil Nelson, US and Seong-Yoon Kang, South Korea) E. Pronunciation and language acquisition 19. The acquisition of the English Sound System (Marilyn Vihman, UK) 20. Variables affecting L2 pronunciation development (Pavel Trofimovich, Sara Kennedy, Jennifer Anne Foote, Canada) F. Pronunciation Teaching 21. Intelligibility in Research and Practice: Teaching Priorities (Tracey Derwing and Murray Munro, Canada) 22. The Segmental/Suprasegmental Debate (Beth Zielinski, Australia) 23. Applying theories of learning and language to teaching pronunciation (Graeme Couper, New Zealand) 24. The pronunciation of English as a Lingua Franca (Robin Walker, Spain and Wafa Zoghbor, UAE) 25. Intonation in research and practice: The importance of metacognition (Marnie Reed and Christina Michaud, US) 26. Integrating pronunciation into the language classroom (Isabelle Darcy and Laura Sicola, US) 27. Using orthography to teach pronunciation (Wayne Dickerson, US) 28. Technology and learning pronunciation (Rebecca Hincks, Sweden) Index
Includes bibliographical references and index
Keywords: English language -- Punctuation -- Handbooks, manuals, etc; Handbooks and manuals